In Defence of Political Parties: A Symposium on Jonathan White and Lea Ypi's The Meaning of Partisanship. (November 2018) - Bonotti, Matteo; White, Jonathan; Leman Ypi, Lea; Calder, Gideon; Donovan, Mark; Roberts, Peri; Vincent, Andrew; Williams, Howard
Over the past 10 years, the literature on the normative dimensions of partisanship and party politics has rapidly grown. Yet, however rich and diverse, this literature lacked so far a single text able to comprehensively map the contours of the existing debates and, at the same time, open up a range of future research avenues. Jonathan White and Lea Ypi's The Meaning of Partisanship does an excellent job at fulfilling both tasks. First, it offers a wide-ranging and sustained engagement with key debates in the history of political thought, contemporary democratic theory and analytical political philosophy. Second, it opens up new areas of research ranging from partisanship across time to revolutionary and transnational partisanship. In this symposium, White and Ypi re-examine some of the book's main themes by responding to the commentaries offered by six political theorists.